Biologics in Systemic Lupus Erythematosus: Recent Evolutions and Benefits - Nilima Rajpal Kundnani; Mihaela Codrina Levai; Mihaela-Diana Popa; Claudia Borza; Mihai Iacob; Alexandra Laura Mederle; Alexandru Blidisel (MDPI AG, 2024)
Introduction: Systemic lupus erythematosus (SLE) is a multifaceted autoimmune disorder characterized by significant autoantibodies, particularly targeting nuclear antigens. SLE pathogenesis involves genetic, environmental, and hormonal factors. The disease course includes flares and remission and involves various organs. Recent therapeutic progresses, including biologics, have improved management and prognosis, though the long-term impact of novel therapies remains to be determined. Biologics in SLE: Rituximab, the earliest B-cell-oriented biologic, binds CD20 and depletes CD20+ B cells, leading to remission in some SLE patients. Belimumab is a B-cell-activating factor (BAFF) inhibitor with a recent additional indication for lupus nephritis. The CALIBRATE and BLISS-BELIEVE studies investigated combinations of these drugs with conventional therapies, showing varied efficacy. Ocrelizumab and obinutuzumab, newer CD20-oriented SLE therapies, together with ofatumumab and veltuzumab, are also promising. The latest trials highlight their efficacy and safety. Anifrolumab, targeting type-I interferon receptors, was evaluated in the TULIP 1/2 trials. The ongoing TULIP LTE trial supports the long-term safety and efficacy of anifrolumab. Additionally, the IRIS Phase III trial is exploring anifrolumab for lupus nephritis, showing favorable renal responses. Tocilizumab and secukinumab are being assessed for SLE, with mixed outcomes. Several biologics targeting the C5 complement protein, together with immunomodulators and immunotherapeutics, are also under investigation for potential benefits in SLE. Discussion: Biologics in SLE target specific immune components, aiming to improve disease control and reduce the side effects of conventional therapy. However, trial outcomes vary due to factors like inclusion criteria and trial design. Conclusions: Biotechnology progress enables targeted biologic therapies for SLE, reducing disease activity and improving patients' quality of life.